Auditor Characteristics and Audit Delay: The Moderating Effect of Audit Complexity - Putri Wahyuni; Yulia Saftiana; Imam Asngari (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the effect of auditor characteristics on audit delay, with audit complexity serving as a moderating variable, in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange during 2018–2024. This research addresses the empirical inconsistency in prior studies regarding the influence of auditor specialization, auditor reputation, and auditor switching on audit timeliness in emerging markets, particularly when organizational complexity is considered. Using panel data regression and Moderated Regression Analysis (MRA) on 55 firms with 385 observations, audit complexity is proxied by the number of subsidiaries. The results indicate that auditor specialization and auditor reputation significantly reduce audit delay, whereas auditor switching significantly increases audit delay. Furthermore, audit complexity strengthens the effects of auditor specialization and auditor switching on audit delay, while weakening the effect of auditor reputation. These findings highlight that auditor competency and organizational complexity are critical determinants of reporting timeliness and extend agency theory by emphasizing the moderating role of audit complexity in explaining variations in audit delay.